Combined effect of gallic acid and zinc ferrite nanoparticles on wheat growth and yield under salinity stress - Shao, Qingqin; Ren, Lantian; Ramzan, Musarrat; Hussain, Muhammad Baqir; Datta, Rahul; Almoallim, Hesham S; Ansari, Mohammad Javed; Ehsan, Abdullah (Scientific reports, 2024)
Salinity stress significantly impacts crops, disrupting their water balance and nutrient uptake, reducing growth, yield, and overall plant health. High salinity in soil can adversely affect plants by disrupting their water balance. Excessive salt levels can lead to dehydration, hinder nutrient absorption, and damage plant cells, ultimately impairing growth and reducing crop yields. Gallic acid (GA) and zinc ferrite (ZnFNP) can effectively overcome this problem. GA can promote root growth, boost photosynthesis, and help plants absorb nutrients efficiently. However, their combined application as an amendment against drought still needs scientific justification. Zinc ferrite nanoparticles possess many beneficial properties for soil remediation and medical applications. That's why the current study used a combination of GA and ZnFNP as amendments to wheat. There were 4 treatments, i.e., 0, 10 µM GA, 15 μM GA, and 20 µM GA, without and with 5 μM ZnFNP applied in 4 replications following a completely randomized design. Results exhibited that 20 µM GA + 5 μM ZnFNP caused significant improvement in wheat shoot length (28.62%), shoot fresh weight (16.52%), shoot dry weight (11.38%), root length (3.64%), root fresh weight (14.72%), and root dry weight (9.71%) in contrast to the control. Significant enrichment in wheat chlorophyll a (19.76%), chlorophyll b (25.16%), total chlorophyll (21.35%), photosynthetic rate (12.72%), transpiration rate (10.09%), and stomatal conductance (15.25%) over the control validate the potential of 20 µM GA + 5 μM ZnFNP. Furthermore, improvement in N, P, and K concentration in grain and shoot verified the effective functioning of 20 µM GA + 5 μM ZnFNP compared to control. In conclusion, 20 µM GA + 5 μM ZnFNP can potentially improve the growth, chlorophyll contents and gas exchange attributes of wheat cultivated in salinity stress. More investigations are suggested to declare 20 µM GA + 5 μM ZnFNP as the best amendment for alleviating salinity stress in different cereal crops.
Keywords: Salinity; Zinc; chlorofyl; Nanoparticles; Zinc ferrite nanoparticles; salinita; pšenice; Plant Roots; Gallic Acid; Ferric Compounds; Salt Stress; fotosyntéza; Gallic acid; kořeny rostlin; železité sloučeniny; Photosynthesis; Soil; Chlorophyll; nanočástice; kyselina gallová; zinek; Triticum; Chlorophyll content; půda; Growth attributes; solný stres; Antioxidant